Peer–to–Peer Video–On–Demand service in NUWeb. (23rd February 2012) - Teng, Hung–Yi; Huang, Hui–Ching; Hwang, Ren–Hung
Because of the continuing growth of video quality and ease of producing video content, traditional centralised video streaming approaches have difficulty in coping with the increasing users' demand in the age of Web 2.0. On the other hand, Peer–to–Peer (P2P) video streaming that only involve peers cannot guarantee reliable Quality of Service (QoS) because of the transient nature of peers. To achieve both scalability and reliability, we present a proxy–assisted P2P Video–On–Demand (VOD) system based on the Net User's Web (NUWeb). In our system, client nodes are self–organised into a mesh–like P2P system to actively participate in the video delivery. A Grey Relation Analysis (GRA)–based peer selection and a deadline–based piece scheduling are proposed to effectively select suitable parents and timely switch parents to provide high video quality. Based on a structured P2P, proxies are also partially participated as an important assistant to maintain the QoS. The simulation experiments show that our approach can provide low delay, high resilience and high streaming quality.